La relation économique et commerciale sino-marocaine : De la coopération au partenariat stratégique - Rachid Rhattat (L’Année du Maghreb)
Since the 1990s, Morocco has made the opening of its economy a strategic focus of its trade policy. Securely fastened to the European Union, by far its largest trading partner, the Kingdom of Morocco has stepped up trade agreements, especially with emerging powers. Sino-Moroccan bilateral “economic and commercial agreement” signed in Rabat March 28, 1995, and entered into force in 1999. The sustained trade growth has allowed China to become Morocco’s third largest supplier. Cooperation between the two states is clearly evident in the asymmetric nature of trade balances and the almost complete absence of Moroccan products in China. To overcome the simple framework of bilateral cooperation, Rabat and Beijing have expressed an interest in implementing a strategic partnership to increase trade and promote investment. The aim is twofold: first, the partners wish to strengthen economic and trade relations, second they agree that trade imbalances should be redressed, in particular by promoting Chinese direct investment in Morocco in areas of particular economic and strategic interest. If the strategic partnership is built around areas of economic interest, the political and diplomatic dimension has not been forgotten. This paper assesses the extent to which Sino-Moroccan cooperation can evolve in the direction of mutual self-satisfaction, while taking a critical look at their strengths and weaknesses.